Maternal Self-Efficacy, Body Dissatisfaction, dan Postpartum Depression pada Primipara Indonesia - Monisha Sonia Selvan; Endang Retno Surjaningrum (Airlangga University Press, Universitas Airlangga, 2023)
The global prevalence of postpartum depression (PPD) has increased over the past two decades. The vast changes in the social and physical body are two crucial postpartum stressors in first-time mothers that may evoke depressive symptoms. This study aims to determine whether there is a significant effect of maternal self-efficacy (MSE) and body dissatisfaction (BD) towards PPD in primiparous mothers. The survey involved approximately 245 Indonesian primiparous mothers within the postpartum period of 0-12 months. Data was disclosed through PMP S-E, BSQ-8B, and EPDS. Regression analysis showed PPD was simultaneously (R = 0,433; R2 = 0,188; p = 0,00) affected by MSE and BD by 18,8%. PPD was also partially affected by both variables, with BD contributing higher (β = 0,167; p = 0,00) than MSE (β = -0,172; p = 0,00). MSE and BD are predictors of PPD in Indonesian primiparous mothers.